2017
DOI: 10.1590/1807-1929/agriambi.v21n6p433-439
|View full text |Cite
|
Sign up to set email alerts
|

Soil resistance to penetration in cotton rows and interrows

Abstract: A B S T R A C TThe soil physical quality is one of the most determinant factors for the development of any crop. This study aimed to assess the sample representativeness in soil resistance to penetration mappings taken in rows and interrows of the cotton crop, under two soil moisture conditions. Thirty control points were sampled in a cotton field of 91 ha. Soil resistance to penetration and soil moisture were measured at these georeferenced points. Regardless of soil moisture, the sampling position of soil re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(14 reference statements)
1
2
0
Order By: Relevance
“…The soil penetration resistances in the compacted layer were 0.20 MPa, 0.33 MPa, 0.50 MPa, 0.93 MPa and 1.77 MPa, respectively for the densities of 1.2 mg m -3 , 1.3 mg m -3 , 1.4 mg m -3 , 1.5 mg m -3 and 1.6 mg m -3 (Figure 1), at a depth of 0.15-0.20 m. This finding was in agreement with the literature, as values higher than 2 MPa generally prevent the development of most crops (Baio et al 2017). The values in the present study were close to those reported by Foloni et al (2006) The root and shoot dry matter yield increased by 47 % and 50 %, respectively, when the penetration resistance was increased to 0.95 MPa and 0.87 MPa, respectively.…”
Section: Resultssupporting
confidence: 90%
“…The soil penetration resistances in the compacted layer were 0.20 MPa, 0.33 MPa, 0.50 MPa, 0.93 MPa and 1.77 MPa, respectively for the densities of 1.2 mg m -3 , 1.3 mg m -3 , 1.4 mg m -3 , 1.5 mg m -3 and 1.6 mg m -3 (Figure 1), at a depth of 0.15-0.20 m. This finding was in agreement with the literature, as values higher than 2 MPa generally prevent the development of most crops (Baio et al 2017). The values in the present study were close to those reported by Foloni et al (2006) The root and shoot dry matter yield increased by 47 % and 50 %, respectively, when the penetration resistance was increased to 0.95 MPa and 0.87 MPa, respectively.…”
Section: Resultssupporting
confidence: 90%
“…The rainy months are the most limiting, due to the time of evaporation so that the soil reaches the adequate humidity, in order to reduce the problem of its compaction by the route of the sprayer, as Baio et al (2017) affirm. Although the Latosols present excellent physical properties, their inadequate management, through the revolving and the traffic of agricultural machines of concentrated form, has favored their compaction (Valicheski et al, 2012;Ataíde et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is understood that the farmer carries out the spraying under conditions of high soil moisture, leading to higher compaction in the path of the sprayer. The increase in soil density and compaction is mainly related to the traffic of machines (Baio et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Among the physical indicators, the penetration resistance (PR) indicated the level of soil compaction (Baio et al, 2017). A penetrometer (Static Cone, Semeato) took three measurements at each sampled point, at a depth of 20 cm.…”
Section: Physical Indicatorsmentioning
confidence: 99%